Harnessing the B Cell Response in Kidney Transplantation – Current State and Future Directions - Anwar, Imran J.; DeLaura, Isabel F.; Gao, Qimeng; Ladowski, Joseph; Jackson, Annette M.; Kwun, Jean; Knechtle, Stuart J. (Frontiers in Immunology, 2022)
Despite dramatic improvement in kidney transplantation outcomes over the last decades due to advent of modern immunosuppressive agents, long-term outcomes remain poor. Antibody-mediated rejection (ABMR), a B cell driven process, accounts for the majority of chronic graft failures. There are currently no FDA-approved regimens for ABMR; however, several clinical trials are currently on-going. In this review, we present current mechanisms of B cell response in kidney transplantation, the clinical impact of sensitization and ABMR, the B cell response under current immunosuppressive regimens, and ongoing clinical trials for ABMR treatment.